Oral Anticoagulation Therapy : Cases and Clinical Correlation - Kiser, Kathryn (Springer International Publishing : Imprint: Springer, 2017)
This case-based title reviews anticoagulation management strategies available for a wide variety of clinical scenarios. Designed to aid providers of direct patient care on complex clinical decisions regarding appropriate evidence-based therapy options, patient and agent related variables to consider, as well as expert opinion on the topic. Oral Anticoagulation Therapy: Cases and Clinical Correlation will provide clinicians and trainees with clear clinical cases, commentary, and resources to develop their knowledge base, problem-solving skills, and ability to practically apply new knowledge to a variety of clinical situations. Resources provided in cases include valuable figures, tables, and key points designed for the reader to be able to utilize at the point of care.
Keywords: Medicine.; Cardiology.; elektronické knihy; electronic books